HASBI ASH SHIDDIEQY DAN METODE PENAFSIRANNYA - Fikri Hamdani (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
This simple paper describes the idea of Hasbi ash Shiddieqi about the science of the Qur'an and Tafseer. This discussion is analytic descriptive study, with a focus on his works, especially works of his commentary entitled Tafsir Al-Nur. The assessment was done by looking at the development of commentary in Indonesia and it can be concluded that the commentary of Hasbi ash Shiddieqi had progressed from the works of previous commentary, namely in terms of methodology of writing and discussion. Hasbi ash Shiddieqi`s commentary patterned fiqhi because besides known as an mufassir Hasbi ash Shiddieqi also known as faqih with strong thoughts and Indonesia insightful